(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
The aim of the current study was to determine how extraction techniques affected the physical and chemical properties of the essential oils from citrus peels, specifically C.bitter orange and C.lemon. The results of the study were summarized as follows:1- The extraction method using microwave-assisted hydrodistillation without solvents was the best in terms of yield, time, and energy savings compared to the extraction method by pre-treatment with ultrasound and then hydro-distillation and hydro-distillation extraction .2- The essential oil extracted from dried bitter orange peels gave the best extraction yield using microwave-assisted hydro-distillation without solvents, reaching 4.21%, followed by lemon, which reached 2.21%.3- No significant effect was observed between the extraction methods used and the physical properties. While observed, there is a slight significant effect between the extraction methods used and the chemical properties of the C. bitter orange peel essential oil.4-It is noted that there is a slight significant effect between the extraction methods used and the physical and chemical properties of the C. Limon peel essential oil.